GENDER AND SECTOR-BASED DIFFERENCES IN JOB SATISFACTION AMONG BANK EMPLOYEES - Dubey, Archi; Baghel, Dipti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In today’s competitive business environment, job satisfaction (JS) has become a critical focus, particularly for employees in the banking sector, where workloads and transaction volumes are increasing. This study investigates the impact of bank type and gender on job satisfaction among banking employees in slect banks of Chhattisgarh, India, highlighting the importance of human capital in driving performance and competitive advantage. A total of 200 employees from public and private sector banks participated in the study, which utilized Spector’s (1994) 36-item Job Satisfaction Survey to measure job satisfaction levels. The data was analyzed using two-way ANOVA. The findings revealed no significant differences in job satisfaction levels between male and female employees or across different types of banks. However, the interaction between gender and bank type positively influenced job satisfaction. This research underscores the necessity for effective human resource management in the banking sector, as maintaining high levels of job satisfaction is essential for enhancing productivity and profitability, ultimately contributing to the broader economic growth.